Anxiety Of Scrooge In Charles Dickens's Novel A Christmas Carol And Other Holiday Treasures (1843): A Psychoanalytic Approach - HARJANTO, BAYU TRIWI; , Dr. Abdilah Nugroho (2017)
This research aims to analyze Scrooge's anxiety based on Charles Dickens' A Christmas Carol and Other Holiday Treasures, to assert the events had been passed by Scrooge and those events made him anxious in his future life. It is also to reveal the role of dream in making Scrooge more and more anxious by using Psychoanalytic Approach. The type of this research is descriptive qualitative. The researcher gets the data from the novel includes the narration, monologue, and dialogue. The techniques of collecting the data are reading the data repeatedly, taking notes, underlying the important words, arranging the data, selecting the data, and drawing conclusion. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and Kata kunci: anxiety, spirit, psychoanalytic approach, Christmas Carol